Plant-Derived Essential Oils and Aqueous Extract as Potential Ingredients for a Biopesticide: Phytotoxicity in Soybean and Activity against Soybean Mosaic Virus - Carezzano, María Evangelina; Reyna, Pablo Gastón; Accotto, Efrén; Giordano, Walter; Oliva, María de las Mercedes; Rodriguez Pardina, Patricia; Sabini, María Carola (MDPI, 2023)
Soybean mosaic disease, caused by the soybean mosaic virus (SMV), is responsible for major losses in yield and seed quality worldwide. Although resistant cultivars are used for its prevention and control, an alternative strategy could consist of applying environmentally friendly antimicrobial agents, such as extracts and essential oils (EOs) of aromatic plants. This study assessed an extract of Achyrocline satureioides and EOs of Minthostachys verticillata, Origanum vulgare, and Thymus vulgaris in terms of their phytotoxicity in soybean. Since all the concentrations tested were found to be safe, the activity of each product against SMV was then assayed in vivo, i.e., in experimentally infected soybean plants. The parameters measured were plant height, wet weight, and virus titer. All the treated plants had a greater height and weight than those in the viral control group. The EOs of M. verticillata (0.80 mg/mL) and T. vulgaris (0.71 mg/mL) inhibited the production of viral antigens, as determined by an ELISA test. These findings could encourage further studies aimed at developing an effective biopesticide against SMV.